Pengaruh umur panen terhadap susut bobot dan organoleptik buah jambu biji (Psidium guajava L) kristal selama penyimpanan - Haya Fadhila Mufza; Edi Minaji Pribadi; Moh. Ega Elman Miska; Inti Mulyo Arti (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Guava (Psidium guajava L) crystal contains good nutrition with white flesh, crispy flesh texture, and fresh taste. Crystal guava fruit is usually consumed as fresh fruit, so it needs proper postharvest handling to maintain the physical and chemical quality of the fruit. The freshness of crystal guava fruit can be related to the water content in the fruit due to the transpiration process. The transpiration process also impacts changes in fruit weight and organoleptic. This study aims to determine the effect of different harvest ages on weight loss, water content, and organoleptic value of crystal guava during storage. The method used was a single-factor Randomized Block Design. Consisting of 4 levels of treatment, namely harvest age 90, 100, 110, and 120 Days After Anthesis (DAA) with analysis of variance ANOVA and DMRT follow-up test (α=5%), and the organoleptic test was tested with Friedman test. The results showed that the age of harvest had a significant effect on weight loss and had no significant effect on water content during 9 days of storage. The highest value of weight loss on the 9th day of storage was obtained at harvest age of 100 DAA, which was 29.19%, followed by 90 DAA (20.13%), 120 DAA (20.01%), and 110 DAA (19.00%). Then, the highest water content value was obtained at the harvest age of 90 DAA (86.46%), and the lowest at the harvest age of 120 DAA (82.39%). In organoleptic results, texture scores could be maintained 6 to 8 days at harvest age of 90 DAA, almost average aroma obtained a score of 6 at all harvest ages, while taste could be maintained at a score of 6 to 8 days at harvest age of 110 DAA.